SIKAP MASYARAKAT TERHADAP PROGRAM BINA KELUARGA REMAJA (BKR) DI KAMPUNG KB KELURAHAN KAMPUNG TENGAH KECAMATAN SUKAJADI, PEKANBARU - Ismi Noviandira; Wilson Wilson; Sumardi Sumardi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: This study examine the attitude of the community towards the Youth Family Development Program (BKR) in the KB Village, Kampung Tengah Sub-district, Sukajadi District, Pekanbaru. This type of research is descriptive research with a quantitative approach, while the data collection process is carried out through a questionnaire (questionnaire) and disseminated to respondents who are selected as research samples. The sampling technique used in this study was random sampling. The result og this study found that the community’s attitude towards the Youth Family Development Program (BKR) in the KB Village, Kampung Tengah Sub-district, Sukajadi District was quite high. The indicators used in this reseach are cognitive, affective, and conativeKey Words : Community Attitude, Youth Family Development